1995
DOI: 10.1063/1.115098
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of yellow luminescence in GaN

Abstract: We investigated the pressure behavior of yellow luminescence in bulk crystals and epitaxial layers of GaN. This photoluminescence band exhibits a blueshift of 30±2 meV/GPa for pressures up to about 20 GPa. For higher pressure we observe the saturation of the position of this luminescence. Both effects are consistent with the mechanism of yellow luminescence caused by electron recombination between the shallow donor (or conduction band) and a deep gap state of donor or acceptor character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(101 citation statements)
references
References 0 publications
11
90
0
Order By: Relevance
“…The results of the present work allude that this omnipresent native defect is very likely the nitrogen-antisite related defect, and it is the prominent native defect that controls the resistivity of unintentionally doped semi-insulating GaN, just like the EL2 defect ͑related to arsenic antisite͒ in unintentionally doped semi-insulating GaAs. Previous studies have also associated the nitrogen antisite defect ͑N Ga ͒ with deep states at 0.8-1.1 eV below the bottom of the conduction band, 47,48 which agrees well with the 1.0 eV activation energy found in our TDDC measurements of the semiinsulating materials.…”
Section: Interpretation Of Compensation Mechanismssupporting
confidence: 81%
“…The results of the present work allude that this omnipresent native defect is very likely the nitrogen-antisite related defect, and it is the prominent native defect that controls the resistivity of unintentionally doped semi-insulating GaN, just like the EL2 defect ͑related to arsenic antisite͒ in unintentionally doped semi-insulating GaAs. Previous studies have also associated the nitrogen antisite defect ͑N Ga ͒ with deep states at 0.8-1.1 eV below the bottom of the conduction band, 47,48 which agrees well with the 1.0 eV activation energy found in our TDDC measurements of the semiinsulating materials.…”
Section: Interpretation Of Compensation Mechanismssupporting
confidence: 81%
“…7 However, Perlin et al reported that the YL transition was more likely due to deep acceptor levels, though not necessarily carbon related. 8,9 The discrepancy between the two explanations was addressed by Polyakov et al who discussed the likelihood of two overlapping bands responsible for the YL in the context of PL measurements on AlGaN samples of varying composition. 10 Zhang a͒ Author to whom correspondence should be addressed; electronic mail: speck@mrl.ucsb.edu and Kuech then correlated YL to carbon concentration by intentionally doping halide vapor phase epitaxy ͑HVPE͒ grown GaN with propane.…”
Section: Introductionmentioning
confidence: 99%
“…11 One characteristic of GaN observed in photoluminescence ͑PL͒ spectra is yellow luminescence ͑YL͒. [12][13][14][15] Kim et al reported multiphotoninduced PL in the YL band and found that the multiphoton PL excitation ͑PLE͒ spectrum exhibits resonance that is attributable to the mid-gap defect states. 6 Sun et al obtained a large two-photon absorption ͑TPA͒ coefficient below the band gap and demonstrated two-photon-induced YL imaging.…”
mentioning
confidence: 99%